Places between vanishing and appearing compass and sense in the Iraqi Kurdish poetry translator (Journal of the College of Education for Women, 2019)
Longer Kurdish poetry translator important tributary of the tributaries of the Iraqi culture contemporary , and a wealth of knowledge rich experiences of an important segment of the Iraqi people , nicked culturally with the languages and cultures of the neighboring nations have , however, much of this potery under depends on the effect of the Arab form and complex , but suffered marginalization and loss as a result of repression by the governments of the country by successive throughout history , and tried to search that offers a vision on the theme of the place and its implications in the Kurdish poetry translator, through the election of a collection of poems and chisels, vertical than that of quantum poetic enormous , but thenature of the trends of this hair impact in addressing the issue of the place or used as a tool technical component , or a theme , or memory , or a picture , or a symbol vanishing l stage in traditional Kurdish poetry , and began in vanishing stage in modern poetry in different movements and trends , experiences and functional capillary we shorting findings Find it in the following :1. Place in the faded Iraqi Kurdish poetry translator in its traditional , especially in Sufi poetry , because it relates to the themes of divinity and worship and autism , which was louder on the place .2. Is a major theme in the place of Iraqi Kurdish poetry translator, as it was clearly shown to conscience and stationed in Kurdish , as well as the persistence of memory and described in texts and stories .3. Use the Kurdish poetry place aesthetic dimension and the basis for the formation of the glamorous image that employed the imagination and the capacity to take advantage of the nature of the Kurdistan beautiful spring and winter.4. Place as regards the subject of identity and an element of excellence historical, social, and cultural.5. The place was in most Kurdish poetry translator equivalent substantive political issue related to human beings and the existence and dignity and freedom , it has been described the loss of the place, or search for him , is in search of a home or for self or for freedom.6. Place and alienation is capules among the expatriate Kurdish poetry , Tdmanma connotations of nostalgia and longing and desire to return to the embrace of the beloved .7. Employed Kurdish poeryt place a symbol creative , and invested historical knowledge in Mesopotamia ; Because of the Kurdish people is about the first configuration to that civilization , and through the ages successive , as well as the use of symbols linked to the place to indicate the identity of the place , including ( burne ) and ( Walnut ) .8. Income place in the context of attempts to experimentation in the movement of Kurdish poetry , for example the formation of the poem mock Eiffel Tower and Erbil.